3(2x-1)-11x=-3x+5

Simple and best practice solution for 3(2x-1)-11x=-3x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-1)-11x=-3x+5 equation:


Simplifying
3(2x + -1) + -11x = -3x + 5

Reorder the terms:
3(-1 + 2x) + -11x = -3x + 5
(-1 * 3 + 2x * 3) + -11x = -3x + 5
(-3 + 6x) + -11x = -3x + 5

Combine like terms: 6x + -11x = -5x
-3 + -5x = -3x + 5

Reorder the terms:
-3 + -5x = 5 + -3x

Solving
-3 + -5x = 5 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-3 + -5x + 3x = 5 + -3x + 3x

Combine like terms: -5x + 3x = -2x
-3 + -2x = 5 + -3x + 3x

Combine like terms: -3x + 3x = 0
-3 + -2x = 5 + 0
-3 + -2x = 5

Add '3' to each side of the equation.
-3 + 3 + -2x = 5 + 3

Combine like terms: -3 + 3 = 0
0 + -2x = 5 + 3
-2x = 5 + 3

Combine like terms: 5 + 3 = 8
-2x = 8

Divide each side by '-2'.
x = -4

Simplifying
x = -4

See similar equations:

| a+a+a+8+2=6+3+3a+a | | 7x+11=5x+15 | | 3x*2+6x=9 | | 9x+229=4x+129 | | 3e/5=3 | | (3x-6)/(2x-2) | | -2+32=x+14 | | 16=x/6-8 | | x^^2/3=16 | | 8b+4=3 | | ln(x)=4.1+ln(7.9) | | 5x-17=4c+36 | | 1/3t-9=40 | | 3x(x-5)-7x^2+16x=0 | | 3n+13=4 | | t/5-2=10 | | log(-5x)=log(4x-9) | | 5x+5+x=77 | | log-5x=log(4x-9) | | 4x+2(4x-3)=138 | | K^2-3k-2=0 | | p(5)=3x^2+5x-4 | | 5x+9-4x=16 | | Y=ax-C | | 2(n-7)+3= | | 4f+8=8f-12 | | 2x-8x[9-4(x+3)]= | | 16t^2+12t^3=t^5 | | (6x+12)+(9x-4)= | | 50=7x-1 | | 4x+2+3x=2 | | -120-7+-120=-4([8*-10]+7)-11([-4*-10])+9 |

Equations solver categories